P703NO synthetic pathway and oxidative stress in microvascular angina: assessment in red blood cells and plasma. (15th July 2014) - Porro, B; Eligini, S; Veglia, F; Lualdi, A; Squellerio, I; Fiorelli, S; Werba, JP; Tremoli, E; Cavalca, V
Abstract: A decreased nitric oxide (NO) bioavailability and an increased oxidative stress play a pivotal role in different cardiovascular pathologies. Recent studies have shown that red blood cells (RBCs) participate in NO formation in the bloodstream. The aim of this study was to outline the metabolic profile of L-arginine (Arg)/NO pathway and of oxidative stress status in RBCs and in plasma of patients with microvascular angina (MVA), investigating similarities and differences with respect to coronary artery disease (CAD) patients or healthy controls (Ctrl). We determined substrate, products (Arg, L-citrulline and L-ornithine) and inhibitors (asymmetric- and symmetric dimethylarginine and monomethylarginine) of NO synthesis in parallel to reduced and oxidized form of glutathione. MVA patients show alterations in the ability of RBCs to produce NO, based on an increase of NO synthesis inhibitors parallel to that found in plasma and a reduction of NO synthase expression. When summary scores of NO synthesis and oxidative stress were computed, both patient groups were associated with a positive score and a negative NO score. This finding points out to an impairement of the capacity of RBCs to produce NO in a pathological condition characterized mostly by alterations at the microvascular bed with no significant coronary stenosis.